RYR1 and CACNA1S genetic variants identified with statin-associated muscle symptoms. (16th October 2018) - Isackson, Paul J; Wang, Jianxin; Zia, Mohammad; Spurgeon, Paul; Levesque, Adrian; Bard, Jonathan; James, Smitha; Nowak, Norma; Lee, Tae Keun; Vladutiu, Georgirene D
Aim: To examine the genetic differences between subjects with statin-associated muscle symptoms and statin-tolerant controls.Materials & methods: Next-generation sequencing was used to characterize the exomes of 76 subjects with severe statin-associated muscle symptoms and 50 statin-tolerant controls.Results: 12 probably pathogenic variants were found within the RYR1 and CACNA1S genes in 16% of cases with severe statin-induced myopathy representing a fourfold increase over variants found in statin-tolerant controls. Subjects with probably pathogenic RYR1 or CACNA1S variants had plasma CK 5X to more than 400X the upper limit of normal in addition to having muscle symptoms.Conclusions: Genetic variants within the RYR1 and CACNA1S genes are likely to be a major contributor to the susceptibility to statin-associated muscle symptoms.